Dorsal laminectomy for the treatment of lateralised cervical intervertebral disc extrusions in dogs—Prognosis and complications - Gouveia, Diogo; Cherubini, Giunio Bruto (Frontiers in Veterinary Science, 2024)
Objective: Describe the complication rate, expected hospitalisation time and prognosis associated with dorsal laminectomy for the treatment of lateralised cervical intervertebral disc extrusion (IVDE) in dogs. Methods: This is a single-centre retrospective case series study. Databases were reviewed from 2012 to 2022 for dogs that had a dorsal laminectomy to treat a lateralised cervical IVDE. Dogs were excluded if additional surgical techniques were performed, or other comorbidities were found on MRI. Results: 52 dogs were included the study. French bulldogs represented 28.8% of the cohort. Patient median age was 6 years and median weight 15kg. Thirty-five dogs (67.3%) presented clinical signs for <3 days and almost half (44.2%) were ambulatory but presented cervical pain and neurological deficits. Median surgical time was 85 minutes. Minor intraoperative complications were reported in 22 (42.3%), with hypothermia being the most common. Thirteen (25%) needed revision surgery due to persistent cervical pain with (9/13) or without (4/13) neurological deficits. Re-extrusion or persistent extrusion was found in 92.3% of cases needing surgical revision. Median hospitalisation time was 6 days. Forty-seven (90.4%) cases had a good outcome. Conclusions and clinical significance: Despite the relatively high rate of intraoperative complications and cases needing revision surgery, dorsal laminectomy as surgical treatment for lateralised cervical IVDE is still associated with good long-term prognosis in most of cases. Prognosis is good even when revision surgery is necessary but expected hospitalisation time seems to be higher when compared to an alternative surgical technique.